US defense politics the origins of security policy - Sapolsky, Harvey M. 1939-; Gholz, Eugene 1971-; Talmadge, Caitlin (Routledge, 2021)
"This textbook provides an accessible overview of US defense politics for upper-level students. This new edition has been fully updated and revised, with a new chapter on veterans and new material on topics such as cyberwarfare and lobbying. Analyzing the ways in which the United States prepares for war, the authors demonstrate how political and organizational interests determine US defense policy and warn against over-emphasis on planning, centralization, and technocracy. Emphasizing the process of defense policy-making rather than just the outcomes of that process, US Defense Politics departs from the traditional style of many existing textbooks. Designed to help students understand the practical side of American national security policy, the book examines the following key themes: - US grand strategy; - who joins America's military; - how and why weapons are bought; - the management of defense; - public attitudes toward the military and casualties; - the roles of the President and the Congress in controlling the military; - the effects of 9/11 and the Global War on Terror on security policy, homeland security, government reorganizations, and intra- and inter-service relations. The textbook will be essential reading for students of US defense politics, US national security policy and homeland security, and highly recommended for students of US foreign policy, US public policy and public administration."...Provided by publisher
Previous edition: 2017
Includes bibliographical references and index
Keywords: Militärpolitik; Sicherheitspolitik; USA; National security / United States; Civil-military relations / United States; Armed Forces; Appropriations and expenditures; Civil-military relations; Military policy; National security; United States / Armed Forces / Appropriations and expenditures; United States / Military policy